A Study of Meat Freshness Detection using Embedded-based pH Sensor - Rajina R. Mohamed; Razali Yaacob; Mohamad A. Mohamed; Arniyati Ahmad; Munir Tajuddin (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
For the past few years, food safety incidents often occur as a result of food poisoning from various food sources such as in schools, hospitals, night markets, street stalls and the like. When the quality of food is reduced due to the low level of freshness, cleanliness factor, safety and nutrition, it can contribute to health risks. According to World Health Organization, food poisoning ailment is a global problem and almost 1 in 10 people fall ill every year from eating degraded food and 420 000 die as a result. Factors such as cost savings, low awareness on food freshness and busy routine lifestyle aggravate the food poisoning problem. Hence it is important to at least maintain the freshness of the food mainly at the prominent area such as school and hospital. There are many methods used to test the freshness food, such as visual appearance, and also classical olfaction including normal olfactory and Scentometer, which requires trained panels to taste or smell the food samples to ensure the quality or strength of the odor. However, this method is rather subjective, because the human sense of smell and taste is different and may be influenced by the weather and experience. Conventional pH and litmus paper also are the alternatives, however the material itself is easily damaged and not suitable for the color blind person. In this paper, we presented raw meat examination using pH sensor based on food acidity. Examination of food freshness level is much easier using pH sensor since it is more practical to be used by consumers at home since it can be mobile, long lived, and accurate embedded-based application. Some testing has been conducted on sensor capability reacting with several buffer solutions on meat samples left at room temperature at various periods of time. Generally, the embedded pH sensor developed has successfully tested raw meat freshness level based on acidity level of meat.